Semantic processing in children 0 to 6 years of age: an N400 analysis - Lindau, Tâmara Andrade; Giacheti, Célia Maria; Silva, Isabella Bonamigo Da; Souza, Deisy Das Graças De (ABRAMO Associação Brasileira de Motricidade Orofacial, 2017)
ABSTRACT This study consists of a literature review about the semantic processing in children 0 to 6 years of age and an N400 data analysis. Twenty-four studies that met the eligibility criteria were found. Most studies aimed to investigate and characterize the electrophysiological patterns of younger children as compared to those found in older children and adults. A large variability of employed experimental tasks was found, showing that there are various investigation alternatives in this perspective. In general, the joint analysis of the results pointed out that despite the different objectives, types of experimental tasks and degrees of language skills (i.e., typical development or different conditions), age was a relevant factor in establishing the presence or not of the N400 effect and its lateralization. When present, the N400 effect showed that the latency and amplitude of the wave decline according to age. However, the variability of procedures can affect the degree of control and the data reliability. For further studies, the development of a standard protocol to investigate the semantic processing by means of the N400 effect data in different populations is an important step and a strong recommendation for the area.

RESUMO Este estudo consiste em uma revisão da literatura sobre o processamento semântico em crianças de zero a seis anos de idade, analisando dados do N400. Foram encontrados 24 estudos que atenderam aos critérios de elegibilidade. A maior parte dos estudos teve por objetivo investigar e caracterizar o padrão eletrofisiológico de crianças mais novas em relação ao padrão encontrado em crianças mais velhas e adultos. Foi encontrada grande variabilidade de tarefas experimentais empregadas, mostrando diversas alternativas de investigação nesta perspectiva. De forma geral, a análise conjunta dos resultados indicou que, apesar dos diferentes objetivos, tipos de provas experimentais e diferentes graus de habilidade de linguagem (i.e., desenvolvimento típico ou diferentes condições), a idade foi um fator relevante na definição da presença ou não e lateralização do efeito N400. Quando ocorreu, o efeito N400 mostrou que a latência e a amplitude da onda declinam com a idade. No entanto, a variabilidade de procedimentos pode afetar o grau de controle e a confiabilidade dos dados. Para estudos futuros, o desenvolvimento de um protocolo padrão para a investigação do processamento semântico, por meio de dados do efeito N400, em diferentes populações é um passo importante e uma forte recomendação para a área.
Processamento semântico em crianças de zero a seis anos de idade: uma análise com o N400
Keywords: Semantics; Evoked Potentials; Electrophysiology; Child; Review; Semântica; Potenciais Evocados; Eletrofisiologia; Criança; Revisão